Long noncoding RNA ZNF800 suppresses proliferation and migration of vascular smooth muscle cells by upregulating PTEN and inhibiting AKT/mTOR/HIF-1α signaling. (November 2020) - Lu, Yuan-Bin; Shi, Chao; Yang, Biao; Lu, Zhi-Feng; Wu, Yi-Lin; Zhang, Ru-Yi; He, Xin; Li, Li-Min; Hu, Bing; Hu, Yan-Wei; Zheng, Lei; Wang, Qian
Abstract: Background and aims: Long noncoding RNAs (lncRNAs) have recently been implicated in many biological and disease processes, but the exact mechanism of their involvement in atherosclerosis is unclear. The aberrant proliferation and migration of vascular smooth muscle cells (VSMCs) is a major contributor to the development of atherosclerotic lesions. This study aimed to investigate the potential effects of lncRNA ZNF800, a previously uncharacterized lncRNA, on VSMC proliferation and migration. Methods: The expression of lncRNA ZNF800 in atherosclerotic plaque tissues was detected using reverse transcription–quantitative PCR (RT-qPCR), while the role and mechanism of lncRNA ZNF800 in proliferation and migration of VSMCs were investigated by CCK8 assay, transwell assay, scratch wound assay, RT-qPCR and Western blot. Results: We found that lncRNA ZNF800 was significantly more abundant in atherosclerotic plaque tissues, and substantially suppressed the proliferation and migration of VSMCs. LncRNA ZNF8 00 had no effect on phosphatase and tensin homolog deleted on chromosome 10 ( PTEN ) mRNA expression but dramatically increased the levels of PTEN protein. Enhanced lncRNA ZNF800 expression inhibited the activity of the AKT/mTOR/HIF-1α signaling pathway, downregulated the expression of vascular endothelial growth factor α (VEGF-α) and matrix metalloproteinase 1 (MMP1), and suppressed VSMC proliferation and migration. These inhibitory effects of lncRNA ZNF800 were abolished by knockdown of PTEN. The inhibitory effects of lncRNA ZNF800 on cell proliferation and migration and the expression of VEGF-α and MMP1 were exacerbated by HIF-1α knockdown in VSMCs. Conclusions: These findings demonstrated that lncRNA ZNF800 suppressed VSMC proliferation and migration by interacting with PTEN through a mechanism involving AKT/mTOR/HIF-1α signaling. Therefore, it may play a key atheroprotective role and represent a potential therapeutic target for atherosclerosis-related diseases. Graphical abstract: Image 1 Highlights: LncRNA ZNF800 is upregulated in atherosclerotic plaques. LncRNA ZNF800 suppresses vascular smooth muscle cells (VSMCs) proliferation and migration by upregulating PTEN expression. LncRNA ZNF800 represses AKT/mTOR/HIF-1α pathway through interaction with PTEN. LncRNA ZNF800 inhibits VSMC proliferation and migration by downregulating HIF-1α expression.